Electrophysiological Basis for Early Repolarization Syndrome - Casado Arroyo, Rubén; Sieira, Juan; Kubala, Maciej; Latcu, Decebal Gabriel; Maeda, Shigo; Brugada, Pedro (Frontiers in Cardiovascular Medicine, 2018)
During last centuries, Early Repolarization pattern has been interpreted as an ECG manifestation not linked to serious cardiovascular events. This view has been challenged on the basis of sporadic clinical observations that linked the J-wave with ventricular arrhythmias and sudden cardiac death. The particular role of the this characteristic pattern in initiating ventricular fibrillation has been sustained by clinical descriptions of a marked and consistent J-wave elevation preceding the onset of the ventricular arrhythmia. Until now, Early Repolarization syndrome patients have been evaluated using ECG and theorizing different interpretations of the findings. Nonetheless, ECG analysis is not able to reveal all depolarization and repolarization properties and the explanation for this clinical events. Recent studies have characterized the epicardial substrate in these patients on the basis of high-resolution data, in an effort to provide insights into the substrate properties that support arrhythmogenicity in these patients. An overview for the current evidence supporting different theories explaining Early Repolarization Syndrome is provided in this review. Finally, future developments in the field directed towards individualized treatment strategies are examined.